PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DIBAGIAN PRODUKSI (Studi Kasus pada PT. Gatra Mapan Ngijo Karangploso) - Ida Ismawati; Abdul Qodir Djaelani; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe purpose of this study is to determine the effect of motivation and work discipline on employee performance. Methods of data analysis in this study using quantitative methods with data processing techniques using multiple regression analysis. Data were collected through questionnaires. Questionnaires distributed to employees of production at PT. GatraMapanNgijokarangploso. Measurements are made with Likert scaled one to five. The results showed no significant effect between motivation on employee performance and also found a significant influence between work discipline on employee performance. Keywords: Motivation, Work Discipline, Employee Performance